Characterisation Of Fusarium Oxysporum Isolated From Various Plants And Non-Agricultural Soils In Malaysia - Abu Bakar, Mohd Hafifi (2020)
Fusarium oxysporum is a cosmopolitan fungus, consists of both pathogenic and non-pathogenic members and well-known as causal agent of several diseases including wilt and rot on various plants. In Malaysia, most studies are focusing on pathogenic isolates of F. oxysporum due to their implications on agricultural production, but less attention was given towards the non-pathogenic isolates. This study attempted to delineate issues of pathogenicity evolution, host specificity and the existence of cryptic species within F. oxysporum from local population.